Sosialisasi ABDIMAS Universitas Primagraha di Kecamatan Tanara (Sektor Pendidikan dan Sektor Perekonomian Budidaya Udang Vaname) - Aimmatul Khazanah; Akmaliyah Akmaliyah; M Syaiful Millah; Siti Ma’ani; Riki Gana Suyatna (Jurnal Bintang Manajemen, 2024)
Primagraha University carries out community service activities in several sub-districts in Serang-Banten which aim to improve student development in the social environment. In this case, UPG sent several students to participate in social life in the community. The materials and methods used in this research are descriptive qualitative methods, this type of research basically uses a deductive-inductive approach. The research location "Socialization of ABDIMAS Primagraha University in the Education Sector and Economic Sector of Vaname Shrimp Cultivation" was carried out in Tanara District, precisely in Kp.Sipanjang Ds.Tenjoayu, Serang-Banten, which is familiar as Kp.Vaname. The research was carried out for approximately three months from September to November 2023. The results of the research were that before carrying out the Community Service's duties, they carried out socialization first in the village sub-district office to get direction in the observations that would be carried out. Where the socialization that will be carried out by ABDIMAS is related to the education sector and the economic sector in the village. Socialization is a process of interaction and learning carried out by a human from birth to the end of his life in a cultural society. The education sector in this area opens our eyes to how much ethics must be applied in the school environment and outside of school. However, the economic sector in the village utilizes existing natural resources, so that its livelihood is in accordance with the characteristics of the village by managing resources from fisheries and then the "BUMDES Sejahtera Bersama" was established to make it easier for the community to develop their livelihoods. From the results of observations as a community servant, socialization is a very important activity so that we remain well connected with the community.